The impact of breathing pulses during core helium burning on the core chemical structure and pulsations of hydrogen-rich atmosphere white dwarfs - Córsico, Alejandro Hugo (2024)
Breathing pulses are mixing episodes that could develop during the core helium-burning phase of low- and intermediate-mass stars. The occurrence of breathing pulses is expected to bear consequences on the formation and evolution of white dwarfs, particularly on the core chemical structure, which can be probed by asteroseismology. We aim to explore the consequences of breathing pulses on the chemical profiles and pulsational properties of variable white dwarf stars with hydrogen-rich envelopes, known as ZZ Ceti stars. We compute stellar models with masses of 1.0M☉ and 2.5M☉ in the zero-age main sequence and evolve them through the core helium-burning phase to the thermal pulses on the asymptotic giant branch, and finally to advanced stages of white dwarf cooling. We compare the chemical structure of the core of white dwarfs whose progenitors have experienced breathing pulses during the core helium-burning phase with the case in which breathing pulses have not occurred. We find that when breathing pulses occur, the white dwarf cores are larger and the central abundances of oxygen are higher than for the case in which the breathing pulses are suppressed, in line with previous studies. However, the occurrence of breathing pulses is not sufficient to explain the large cores and the excessive oxygen abundances that characterize recently derived asteroseismological models of pulsating white dwarfs. We find absolute differences of up to ∼30 s when we compare pulsation periods of white dwarfs coming from progenitors that have experienced breathing pulses with the case in which the progenitors have not suffered breathing pulses.